Accessibility considerations for e learning in Ghana - Boateng, J.K. (My University, 2016)
This paper reports on a study that explored the best ways to design e learning in order to provide better access for adult learners with disabilities. Two districts from the Central Region of Ghana were selected and two major research questions guided the study. The five-point Likert scale was employed between May and August of 2014. The two questions asked were: The kind of issues that should be taken into account in the design and management of accessible e learning? And what problems need be resolved to have accessiibility solutions for e-learning by the diverse adult learner population in the region? The results confirm existing insights about accessibility considerations in Ghana, other African courntries and the world at large for the disabled, showing that Ghana and other African countries are not unique in terms of accessibility requirements in designing e learning in order to provide better access for adult learners with disabilities
Keywords: accessibility, disabled learners, communication handling, learning attainment, web interface accessibility